2019
DOI: 10.1016/j.clinph.2019.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose perampanel improves refractory cortical myoclonus by the dispersed and suppressed paroxysmal depolarization shifts in the sensorimotor cortex

Abstract: h i g h l i g h t sLow dose of perampanel (PER) is tolerable and effective to ameliorate refractory cortical myoclonus. PER suppresses and disperses paroxysmal depolarization shifts directly on the postsynaptic neurons. This action was reflected by temporal dispersion in giant SEPs (a potential clinical biomarker). a b s t r a c tObjective: To elucidate the effects of perampanel (PER) on refractory cortical myoclonus for dose, etiology and somatosensory-evoked potential (SEP) findings. Methods: We examined 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…Abnormal AMPA receptor expression on the cell surface is also known to occur in diseases involving intracellular substance accumulation. The AMPA antagonist perampanel is now recognized as a potentially efficacious drug for progressive myoclonic epilepsies (PME) [112][113][114][115][116][117][118][119][120][121][122][123], a group of rare types of epilepsy, most of which are recognized as intracellular substance storage disorders. Although each of these diseases involves increased intracellular storage of a different pathological substance, their clinical phenotypes are very similar; it is therefore reasonable to consider the existence of several similar AMPA-receptor-related endophenotypes that produce the same clinical phenotype.…”
Section: Genetic Mutations In the Ampa Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal AMPA receptor expression on the cell surface is also known to occur in diseases involving intracellular substance accumulation. The AMPA antagonist perampanel is now recognized as a potentially efficacious drug for progressive myoclonic epilepsies (PME) [112][113][114][115][116][117][118][119][120][121][122][123], a group of rare types of epilepsy, most of which are recognized as intracellular substance storage disorders. Although each of these diseases involves increased intracellular storage of a different pathological substance, their clinical phenotypes are very similar; it is therefore reasonable to consider the existence of several similar AMPA-receptor-related endophenotypes that produce the same clinical phenotype.…”
Section: Genetic Mutations In the Ampa Receptormentioning
confidence: 99%
“…gSEPs are considered to be enlarged synaptic potentials with enhanced synchronism, and are therefore similar to PDS. Oi et al [118] evaluated the effect of perampanel on gSEPs, and found that perampanel reduced gSEP amplitude. Interestingly, perampanel efficacy related to prolonged latency to the P25 and N33 components of gSEP.…”
Section: Synchronized Activitymentioning
confidence: 99%
“…To our knowledge, there has been only one fully published case report [3] describing an improvement of myoclonus in LAS using perampanel (Table 1) [3,[5][6][7]. A recent electrophysiological study reported that improvement in cortical myoclonus with perampanel correlated with improvements in the parameters of giant somatosensory-evoked potentials [7].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perampanel was newly approved as monotherapy for focal epilepsy in Japan in January 2020 [ 8 ]. Recently, the efficacy of low-dose perampanel has been reported in refractory myoclonus in epilepsy patients [ 9 , 10 ]. Perampanel has a good safety profile and is well tolerated, and therapeutic drug monitoring is considered useful since the dose correlates linearly with effect and adverse events [ 11 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%